Multiple repeated sprint ability test for badminton players involving four changes of direction: validity and reliability (part 1) - Phomsoupha, M.; Berger, Q.; Laffaye, G. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was: (a) to develop a new sport-specific, repeated-sprint ability test involving 4 changes of direction, namely, the multiple repeated sprint ability (MRSAB) test for badminton players; (b) to determine its validity by comparing the results of 5 different skill levels; and (c) to assess the link between the new test and neuromuscular lower limb and physiological variables. For this purpose, 42 participants were separated into 5 groups to perform the MRSAB test at the same time of day, on 2 occasions, separated by at least 48 hours. The MRSAB test consisted of 2 repetitions of 4 movements (4 × 3 m) separated by 30 seconds of passive recovery. This pattern was repeated 10 times. The best time (BT), mean time (MT), and fatigue index (FI) were measured. Heart rate and blood lactate concentration were also recorded to determine the participants' physiological responses to the test. The results show that the MRSAB test is valid, because it differentiates between the 5 skill levels for BT, MT and FI and offers a reliable method (intraclass correlation coefficient = 0.95 for BT and MT) for testing badminton players, with no differences between the sessions (p > 0.05). Moreover, the link between MT and neuromuscular variables, such as jump height in squats and countermovements (r = -0.55 and -0.60, respectively) and with VO2max (r = -0.92) reveals that this test uses a combination of the anaerobic and aerobic systems; thus, it can be used by trainers either to improve movement ability or increase these physical qualities.